Comparison of the Effectiveness of Dramatherapy for Clients with Addiction under Treatment - Valenta M.; Krahulcova Ch.; Listiakova I. (Клиническая и специальная психология, 2015)
This paper introduces the means of dramatherapy intervention at two sites - at the Centre for secondary prevention and treatment of addictions Military Hospital in Olomouc and Toxicological rehabilitation department 17B (community Mandala) Psychiatric Hospital in Kroměříž. The first workplace has a detoxifying and short-term intervention program (month), while the Mandala is implemented medium-term dramatherapy program (up to a half-year). The second part gives the results of the investigation, which was focused on finding differences (relations) between the client and the perception of the benefits of the concept dramatherapy intervention at the aforementioned sites - nvestigation did not show differences between evaluation intervention customers of both institutions.